IMMUNOHISTOCHEMICAL EXPRESSION OF THE PROMISING THERAPEUTIC TARGET (HUMAN EPIDERMAL GROWTH FACTOR RECEPTOR 2/NEU) IN IRAQI PATIENTS WITH MEDULLOBLASTOMA - Al Mukhtar, Zainab Khalid; Ali Al Saeg, Zinah Hussein Abed; Hasan, Farah Falah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: With the advent of ongoing novel modalities toward the treatment of human epidermal growth factor receptor 2 (HER2)/NEU - positive malignancies, the serious side effects of chemoradiotherapy have been minimized. Hence, this study was conducted to identify the patterns of immunohistochemical expression of the promising therapeutic target (HER2/NEU) among Iraqi patients with medulloblastoma in an attempt to provide basic histological information's that would help in future clinical researches. Materials and Methods: In this retrospective study, 42 formalin - fixed paraffin - embedded tissue blocks represent cases of surgically removed medulloblastomas were retrieved from the archived materials in a specialized surgical hospital at Bagdad. The histological diagnosis had been revised, and all cases were stained by the immunohistochemical technique with HER2/NEU antibody and assessed independently by three pathologists. Results: Out of 42 cases, only two which represent 4.76% showed positive results manifested by a strong membranous staining when immunohistochemically evaluated using the same scoring system established for HER2/NEU in breast cancer. 14 cases (33.3%) showed incomplete membranous and five cases (11.9%) showed only cytoplasmic reaction patterns. Conclusion: The rate of expression of HER2/NEU in medulloblastoma among Iraqi patients is very low and found only in aggressive anaplastic histological type when immunohistochemically evaluated using the same scoring system established for HER2/NEU in breast cancer. However, a good number of negative cases showed cytoplasmic and incomplete membranous staining patterns highlighting the importance of establishing medulloblastoma - specific HER2/NEU scoring criteria and testing methods to discover the unique feature of expression of this therapeutic target in medulloblastoma. Â